(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
Traveler diarrhea is known as Bali’s belly and is often suffered by foreign tourists who visit Bali Island. These activities aimed to see the diarrhea status and knowledge level of hotel employees of the hand washing method. We held this community devotion at a hotel in the Kalibukbuk District, Buleleng – Bali Province, in April 2023. The objective of these activities was for all the hotel employees, a number 44 people. The subjects were chosen by the total sampling method. The inclusion criteria are the hotel employees were registered and willing to participate. The inclusion criteria are sick and on duty. The data collected are the results of a complete fecal laboratory and the level of knowledge about excellent and correct hand washing. Complete fecal data was collected by observation, while knowledge level data was collected by the self-administered questionnaire method. Furthermore, the data were analyzed in a univariate descriptive. Of the forty-four service participants, twenty-one were willing to collect fecal samples. The results of laboratory tests were obtained 100% of the hotel staff had complete fecal results within normal limits based on indicators of color, texture, fecal consistency, the appearance of bacteria, fungi, parasites, viruses, blood, lenders, pus, meat fiber, sugar and fat in feces and potential fecal, hydrogen (pH). The staff’s knowledge level score about handwashing increased from 75.7 before counseling to 99.2 after counseling. Hotel employees are free from traveler’s diarrheal disease and their level of knowledge increases after being given a campaign on proper and correct handwashing methods. So, it is advisable to routinely conduct fecal examinations once every one year and keep. Updating the knowledge and skills of staff in washing hands appropriately and correctly as an effort to prevent disease, especially travelers’ diarrhea.